ANALISIS FAKTOR PENGHAMBAT DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA KELAS IVA SEKOLAH DASAR INPRES FATUKOA KOTA KUPANG - Fulgensiana Baru; Chintia M.P Ati; Cornelia A. Naitili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the inhibiting factors in the formation of disciplined character among Grade IVA students at SD Inpres Fatukoa, particularly in terms of time discipline and learning discipline, as well as to identify teachers’ efforts in overcoming these obstacles. This research employed a qualitative descriptive approach. The subjects consisted of the principal, classroom teacher, and Grade IVA students, while the object of the study was the inhibiting factors of discipline character formation. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings show that the inhibiting factors of students’ disciplined character formation originate from both internal and external sources. Internal factors include low learning motivation, procrastination habits, and lack of self-awareness. External factors comprise limited parental supervision, negative peer influence, inconsistency in rule enforcement at school, excessive use of technology, and environmental conditions. Teachers’ efforts to overcome these obstacles are carried out through role modeling of discipline, habituation and positive reinforcement, as well as collaboration with parents and the school community. The study concludes that forming students’ disciplined character requires active teacher involvement, parental support, and consistent school policies. This research is expected to serve as both evaluation material and a reference in developing character education strategies in elementary schools.